Bicycle Design: A different approach to improving on the world human powered speed records - Epema, H. K.; van den Brand, S.; Gregoor, W.; Kooijman, J. D. G.; Pereboom, H. P.; Wielemaker, D. C.; van der Zweep, C. -J. (Procedia Engineering, 2012)
The current International Human Powered Vehicle Association world records for faired bicycles stand at 133.284 km/h for the 200m flying start speed record and 91.562 km for the hour record. Traditionally the recumbent bicycles that have been developed for breaking one of either of these records have been optimized around a specific, relatively small rider, enabling the overall size to be kept small. Creating the smallest frontal area possible and optimal aerodynamic shape were then the design goals. This paper discusses the development of the Velox recumbent bicycle, which has been designed using another approach. The power required to break either of the records depends mostly on air resistance. Therefore small riders have the advantage of allowing for smaller frontal areas, whilst larger riders are able to provide more power. Performance optimization, lead to a design based around an average 1.95m tall male rider for Velox. The aerodynamic shape of Velox was then developed around the above criterion and designed with CFD and validated with wind tunnel and road tests. Essential for the rider's performance is that the rider feels comfortable whilst riding the bicycle. Therefore the uncontrolled lateral dynamics and the required rider steer control input were investigated. The bicycle's geometry was optimized for low speed stability and the required control input.